Pengaruh Citra Merek, Kualitas Produk, Dan Harga Terhadap Keputusan Pembelian Konsumen Pada E-Commerce Tokopedia (Studi Kasus Pada Mahasiswa FEB UNISMA Angkatan 2019) - Subhan Subhan; Agus Widarko; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research was conducted to find out and analyze the effect of brand image, product quality, and price on consumer purchasing decisions on Tokopedia e-commerce witth a casw study on students of the Faculty of Economics and Business, Islamic University of Malang class of 2019 who were selected by purposive sampling and determining the number of samples using the Malholtra formula. The number of samples used in this research were 65 respondents. Data analysis methods used in this research are Validity test and Reliability test, Normality Test, Multicollinearity test and Heteroscedasticity test, Multiple Linear Regression Analysis, Hypothesis Test, and Determination Coefficient Test (Adjusted R2). Process analysis using SPSS. The results of the study state that brand image, product quality, and price simultaneously influence consumer purchasing decisions and partially brand image, product quality, and price have a positive and significant effect on consumer buying decisions. Keywords: Brand Image, Product Quality, Price, Consumer Purchase Decision